Does Influencers Popularity Actually Matter? An Experimental Investigation of the Effect of Influencers on Body Satisfaction and Mood Among Young Chinese Females: The Case of RED (Xiaohongshu) - Zhang, Xiaoxiao; Zhu, Wuchang; Sun, Shaojing; Chen, Jingxi (Frontiers in Psychology, 2021)
Idealized body images on social media have been linked to negative psychological wellbeing among young females by many studies. However, social media influencers’ imagery has not attracted much research attention in either the Western or Asian context. This study aimed to experimentally investigate the impact of high versus low popular social media influencer images on Chinese young females’ body satisfaction and mood. Participants were 420 female RED users (aged 18-35) who were randomly assigned to three groups: (1) a set of high popular influencers’ body postings; (2) a set of low popular influencers’ body postings; and (3) a control set of nature images. The results revealed that exposure to two influencer imagery groups led to lower body satisfaction and negative mood compared with the control group (natural images). Notably, these comparison revealed no significant difference between the low-influencer group and high-influencer group on body satisfaction and mood. Additionally, this effect was moderated by individuals’ self-discrepancy between personal ideal and own body. That is, exposure to idealized body images does not always produce negative effects. For those who with lower self-discrepancy, idealized body posts rather positively affected their own body satisfaction. The current research contributes to the media effect literature by providing important new insights into the study of body image in the context of China.